Surgical Tactics to Cervical Myelopathy and Radiculopathy - Junichi Mizuno (Neurologico Spinale Medico Chirurgico, 2018)
There are 2 ways to approach the cervical spine, the anterior approach and the posterior approach. When conservative treatments fail, surgical management is brought to the table. The key issues to determine the approach include good outcome, less axial pain, and preservation of the motion. Minimally invasive techniques can provide good outcome with fewer complications. Anterior decompression and fusion (ACDF) is the gold standard technique since 1950s, and ACDF is now performed under the microscope. Skin-fold incision, longitudinal dissection of the platysma and gentle retraction of the trachea, esophagus, as well as vessels, expose the anterior surface of the vertebral bodies. After satisfactory decompression, the interbody fusion is performed. Key-hole discectomy is less-invasive procedure without metal fixation. This unique procedure is indicated to the unilateral radiculopathy in young patients. As for posterior approach, a conventional laminectomy is just destructive with delayed kyphosis. In order to reduce this serious complication, laminoplasty has been performed particularly in Japan since the 1980s. There are open-door and double-door laminoplasty in this technique, and the decision is made mainly by surgeons’ preference. Laminoplasty is good for multi-level spondylosis and ossification of the posterior longitudinal ligament (OPLL). The spacer for this approach consists of metal in most cases. Percutaneous endoscopic cervical foraminotomy (PECF) is chosen in cases of unilateral radiculopathy. In this presentation, various surgical techniques to the cervical degenerative disease are shown with advantages and pitfalls and the importance of minimally invasive surgery is stressed, based on my clinical experience.